2015
DOI: 10.1016/j.conbuildmat.2015.08.137
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of sustainable hybrid-synthetic fiber reinforced cellular light weight concrete for structural applications of masonry

Abstract: Cellular light weight concrete (CLC) masonry has gained tremendous popularity in recent decades owing to its sustainability, density, low thermal conductivity and use of less mortar joints. The objective of this study is to develop a high performance fiber reinforced cellular concrete to provide a better alternative than aerated autoclaved concrete blocks for structural applications of masonry. Use of micro-fibers (Fibrillated) enhances pre-cracking behavior of masonry by arresting cracks at micro-scale, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Higher compressive strength was obtained for a specimen with higher fiber dosage (6 kg/m 3 ), whereas the lowest value was obtained in control specimen. Previous studies by authors (Rasheed and Prakash 2015) on cellular lightweight concrete have indicated that the fiber dosage of about 4-5 kg/m 3 is the optimum dosage beyond which there is not much strength increase. However, with an increase in temperature there is a decrease in the peak compressive strength.…”
Section: Residual Compressive Stress-strain Behaviourmentioning
confidence: 93%
“…Higher compressive strength was obtained for a specimen with higher fiber dosage (6 kg/m 3 ), whereas the lowest value was obtained in control specimen. Previous studies by authors (Rasheed and Prakash 2015) on cellular lightweight concrete have indicated that the fiber dosage of about 4-5 kg/m 3 is the optimum dosage beyond which there is not much strength increase. However, with an increase in temperature there is a decrease in the peak compressive strength.…”
Section: Residual Compressive Stress-strain Behaviourmentioning
confidence: 93%
“…Therefore, the unit of TTI and CTI will be those of energy per unit volume that is N-mm per cubic millimeter which turns out to be MPa. Complete details of uniaxial compression and tension tests and results can be found elsewhere [8], [10]. [39] and JCI [40] standards has given test procedures for determination of fracture parameters of concrete.…”
Section: Siliceous Fly Ash Of Class F Is Used and Its Basic Chemical mentioning
confidence: 99%
“…Fiber reinforced CLC (FRCLC) is one such special concrete which has enhanced toughness, better composite behavior, durability and impact resistance compared to their unreinforced counterpart [6], [7]. Improvement of mechanical properties of high performance concrete by addition of synthetic fiber reinforcement has been confirmed by many researchers [8]- [12]. Although steel fibers have superior mechanical properties compared to that of synthetic fibers, they decrease the workability and creates a balling effect at higher dosage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber Reinforced Concrete (FRC) is tailored by addition of randomly oriented fibers to plain concrete. FRC has gained popularity in the recent years due to advantages like (i) ease of availability of fibers; (ii) better performance in serviceability regime; and (iii) improved mechanical properties in compression, tension, flexure, and shear when compared to the conventional concrete [1][2][3][4][5]. Apart from crack resistance, steel fibers can also be used to replace the conventional transverse reinforcement in the concrete [6,7].…”
Section: Introductionmentioning
confidence: 99%